PSIX-10 The replacement of corn by soybean molasses improves ruminal environment of feedlot sheep - Pereira-Junior, Sérgio A G (J Anim Sci, 2019)
The goal of this study was to assess the effects of increasing levels of soybean molasses (SM) on ruminal parameters of feedlot sheep. Nine crossbred ruminally-cannulated male sheep (73.3 ± 2.5 kg BW) were randomly distributed in a triple 3 × 3 Latin square design. The treatments consisted of isonitrogenous (18% CP) and isoenergetic (2.7 Mcal/kg) diets, containing 0, 15 or 30% SM (DM basis). After 14 d of adaptation period, rumen fluid samples were collected in each experimental period, at 0, 2, 4, 6, 8 and 10 h after feeding, to evaluate ruminal pH, NH(3)-N and VFA concentrations. The pH was measured immediately after rumen fluid sampling, and NH(3)-N concentrations were determined with micro-Kjeldahl apparatus. The concentration of VFA was assessed by gas chromatography. Data were evaluated using the MIXED procedure of SAS, with repeated measures over time. Orthogonal contrasts were used to determine the linear and quadratic effects of SM inclusions, as well as the contrast Control × SM treatments. There was no interaction of time of sampling × treatment for all variables evaluated (P > 0.05). The inclusion of SM increased linearly (P = 0.02) the ruminal pH (5.92 to 5.21 – 0 and 30%, respectively), and decreased linearly (P = 0.006) the NH(3)-N concentration (32.19 to 21.78 mg/dL – 0 and 30%, respectively). The addition of SM did not alter most of VFA, with exception for valeric acid (quadratic, P = 0.05), with the higher value observed in 15% SM-fed animals (1.33 mMol/L). However, when the percentage of each VFA was evaluated, the inclusion of SM increased linearly the butyric acid (P = 0.05), from 14.1 to 16.9%. The results indicate that the inclusion of soybean molasses at up to 30% (DM basis) improves the ruminal fermentation of diets in feedlot crossbred sheep. [Image: see text] [Image: see text]